2011
DOI: 10.1165/rcmb.2010-0253oc
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Nucleotide and Mucin Hypersecretion from Goblet-Cell Metaplastic Human Airway Epithelium

Abstract: Adenosine triphosphate (ATP) and its metabolite adenosine regulate airway mucociliary clearance via activation of purinoceptors. In this study, we investigated the contribution of goblet cells to airway epithelial ATP release. Primary human bronchial epithelial (HBE) cultures, typically dominated by ciliated cells, were induced to develop goblet cell metaplasia by infection with respiratory syncytial virus (RSV) or treatment with IL-13. Under resting conditions, goblet-cell metaplastic cultures displayed enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 50 publications
(72 reference statements)
2
54
0
Order By: Relevance
“…Because Entpd7 was highly expressed in goblet cells, as well as absorptive ECs, it is possible that Entpd7 is expressed in the membrane of mucin-containing vacuoles of goblet cells to control ATP levels in the vacuole. Given that goblet cells of the airway were shown to secrete ATP, as well as mucin (42), intestinal goblet cells might be a major source of luminal ATP, the level of which is closely regulated by ENTPDase7.…”
Section: Discussionmentioning
confidence: 99%
“…Because Entpd7 was highly expressed in goblet cells, as well as absorptive ECs, it is possible that Entpd7 is expressed in the membrane of mucin-containing vacuoles of goblet cells to control ATP levels in the vacuole. Given that goblet cells of the airway were shown to secrete ATP, as well as mucin (42), intestinal goblet cells might be a major source of luminal ATP, the level of which is closely regulated by ENTPDase7.…”
Section: Discussionmentioning
confidence: 99%
“…At lower concentrations, the H 2 O 2 stimulation of CFTR to increase mucociliary clearance occurs concomitantly with increases in CBF (2) through Ca 21 -mediated and cAMP-mediated stimulation. In addition, mucins are also likely secreted through a Ca 21 -mediated mechanism (48). It is interesting to speculate that H 2 O 2 production by epithelial cells contributes to the normal ASL volume increases that accompany the Ca 21 -mediated stimulation of CBF and mucin secretions in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we recently demonstrated that plasma membrane pannexin 1 largely contributes to conductive ATP release from normal airways dominated by ciliated cells (22). Deletion of the pannexin 1 gene resulted in impaired ATP release in mouse tracheas ex vivo (22).We also demonstrated that mucin granules are an important additional source of nucleotide release (8,9,18). That is, primary cultures of human airway epithelial cells that were induced to develop goblet cell hyperplasia via respiratory syncytial virus infection or IL-13 exposure acquired enhanced ATP release from the secretory pathway that correlated with increased mucin secretion and was not affected by pannexin inhibitors (18).…”
mentioning
confidence: 82%